Identification of Enterococcus faecalis antigens specifically expressed in vivo - Chetana S. Makade; Pratima R. Shenoi; Elakshi Morey; Ameya V. Paralikar (Korean Academy of Conservative Dentistry, 2017)
Objectives Literature has shown that micro-organisms contaminate gutta percha (GP) during storage and manipulation. Till date herbal extracts are not explored as an alternative medicament for pre-operative chairside disinfection of GP cones. The purpose of our study was to evaluate the antimicrobial activity and efficacy of lemon grass oil (LG), basil oil (BO), and obicure tea extract (OT) in disinfecting GP cones before obturation. Materials and Methods Agar diffusion method was used to evaluate the antimicrobial efficacy of LG, BO, OT, and sodium hypochlorite (control) against common contaminants, namely, Enterococcus faecalis, Staphylococcus aureus, and Candida albicans. One hundred and twenty GP cones were contaminated and cut into 2. First half was placed in the broth and incubated; whereas the second was treated with herbal extracts for 1 minute and then incubated for 24 hours in the broth. Any inhibition in bacterial growth was noted with presence/absence of turbidity. Two-way analysis of variance and χ2 test were used to assess the effectiveness of herbal extracts to decontaminate GP. Results LG showed the highest inhibition zones (29.9 ± 6.9 mm) for all tested organisms, followed by OT extract (16.3 ± 1.8 mm), sodium hypochlorite (16.0 ± 1.6 mm), and BO (14.5 ± 5.3 mm). Statistically significant difference was observed between LG and other herbal extracts (p < 0.05). Conclusions All extracts proved to be potential rapid chairside disinfectants of GP cones with LG showing the highest antimicrobial activity.